Prevalence of Autoimmune Diseases in Patients Treated With Immune Checkpoint Inhibitors: An Epidemiological Study Using A Global Network of Health Care Organizations - Pushti Khandwala; Devashish Desai; Arthur Lau (ACR Open Rheumatology)
Objective Evaluate prevalence of new onset autoimmune conditions (ACs) after commencement of immune checkpoint inhibitors (ICIs). Methods This retrospective observational study was done using TriNetX. Patients with neoplasm for which ICIs were approved were stratified into two groups based on ICI use. Multivariate Cox proportional hazard models and Kaplan Meier method were used to assess risk of developing ACs among the groups. Subgroup analysis was done to evaluate risk of ACs in patients receiving cytotoxic T‐lymphocyte‐associated protein 4 inhibitor (CTLA4i) versus program cell death protein 1 inhibitor (PD1i) and program death ligand 1 inhibitor (PDL1i) inhibitors and combination treatment (CT) (CTLA4 + PD1i/PDL1i) versus PD1i/PDL1i. Results Patients who received ICIs (2.03% of total population) were younger (68.7 ± 12.6 vs 71.8 ± 13.9; P < 0.001), predominantly male (54% vs 41%; P < 0.0001), and White (68% vs 58%; P < 0.0001), had lower odds of developing systemic lupus erythematosus (SLE) (0.366% vs 0.437%, odds ratio [OR] 0.837; P = 0.0005) and systemic sclerosis (0.108% vs 0.135%, OR 0.796; P = 0.0151), and had higher odds of developing rheumatoid arthritis (RA) (2.194% vs 1.752%, OR 1.258; P < 0.0001 with hazard ratio 1.746; P < 0.0001). There was no significant difference in developing vasculitis, dermatopolymyositis, and psoriatic arthritis when compared to patients who did not receive ICIs. The prevalence of ACs remained true after propensity score matching, except that there was no difference compared with the prevalence of SLE (0.37% [n = 391] vs 0.393% n = 415], OR 0.942 [0.82–1.082]; P = 0.3970). Conclusion Patients receiving ICIs have an increased risk of developing ACs, especially RA. There needs to be a high index of suspicion and awareness about ACs for prescribers of ICIs.